Siti Manggopoh: Women Warriors From The Coastal Land of Minangkabau in The 1908 Balasting War - Siti Fatimah (Social Studies Conference Proceedings, 2022)
Morphologically and culturally, West Sumatra's region, more popularly known as Minangkabau, is divided into land areas (darek) and coastal areas (rantau). These two regions have quite different characters, including their people. The Blasting War was a tough period for the Indonesian people, including for West Sumatra. Almost all areas in West Sumatra resisted physical occupation at that time. One area that was very resistant at that time was Agam Regency. Interestingly, the leader of this resistance movement was a woman named Siti Manggopoh. This paper aims to; (1) reconstruct the figure of Siti Manggopoh as a leader of the Blasting war struggle from the coastal lands of Minangkabau; (2) analyze family, socio-cultural, and geographical background on Siti's attitude and strategy against colonialism; (3) expressing the views and perceptions of the people of West Sumatra, especially Agam towards the figure of Siti as a warrior. This study uses historical methods, especially oral history methods, with heuristic, criticism, analysis, and historuigraphic steps. This research is also strengthened by an interdisciplinary approach, especially a geographical approach. The research findings reveal that the typology of Siti Manggopoh's struggle is strongly influenced by the cosmopolistic and egalitarian characteristics of coastal culture. The people of West Sumatra, especially the people of Manggopoh really hope that Siti will become a national hero. Therefore, they gave Siti the nickname of the Lioness of the Coastal Lands.